Activity, Process, Continuant, Substance, Organism. (26th January 2016) - Wiggins, David
Abstract: This paper is a response to the suggestion that processes provide a better framework for interpreting science, biological science especially, than do substances . The philosopher of substance is ill-prepared, it has been suggested, for the question 'how a combination of processes can maintain the appearance of stability and persistence in an entity that is fundamentally only a temporary eddy in a flux of change'. In response, I defend a plural ontology of process, activity, event and continuant, and show how a sortalist philosophy of substance that makes Hilary Putnam's distinction of 'realism' from 'metaphysical realism' can treat disputed questions concerning the identity and individuation of colonial siphonophores, slime moulds and plant-colonies.